A combined heterotrophic and sulfur-based autotrophic process to reduce high concentration perchlorate via anaerobic baffled reactors: Performance advantages of a step-feeding strategy. (May 2019) - Li, Kun; Guo, Jianbo; Li, Haibo; Han, Yi; Chen, Zhi; Song, Yuanyuan; Xing, Yajuan; Zhang, Chunqing
Graphical abstract: Highlights: The combined heterotrophic and autotrophic process was investigated in ABR. A high perchlorate reduction rate was obtained by step-feeding strategy. The combined heterotrophic and autotrophic process decreases sulfate production. The tryptophan-like materials can promote heterotrophic perchlorate sludge activity. Relationships between dominant microbes and the environment were found by PCA. Abstract: The combined anaerobic baffled reactors (ABRs) of heterotrophic and sulfur-based autotrophic processes were first investigated for the removal of high perchlorate concentration under different feeding strategies. The removal efficiency of the step-feeding ABR (SF-ABR) reached 97.56% at 800 mg/L perchlorate, which was significantly superior to the normal-feeding ABR (NF-ABR). In three components of the extracellular polymeric substances (EPS), the fluorescence intensity of the tryptophan-like component were identified by fluorescence excitation–emission matrix (EEM) spectra with parallel factor (PARAFAC) analysis, and exhibited a positive relationship with the perchlorate removal rate in the heterotrophic perchlorate reduction unit (HPR unit) of the SF-ABR ( R 2 = 0.9791) and NF-ABR ( R 2 = 0.9860). Bacterial community analysis suggested the dominating perchlorate reducing bacteria and the diversity in two ABRs. Principal component analysis indicated that the electron donor affected the microbial community structures. The study confirms that the SF-ABR is a powerful bioreactor for the combined heterotrophic and sulfur-based autotrophic process.